USING DREAMWORKS ANIMATION VIDEOS TO IMPROVE THE ELEVENTH GRADERS’ ABILITY IN WRITING NARRATIVE TEXT (RETAIN, 2014)
USING DREAMWORKS ANIMATION VIDEOS TO IMPROVE THE ELEVENTH GRADERS’ ABILITY IN WRITING NARRATIVE TEXT Firdausi Nuzula English Education Study Program, Faculty of Language and Arts, Surabaya State University click_legolas@yahoo.com Dra. Theresia Kumalarini, M.Pd English Education Study Program, Faculty of Language and Arts, Surabaya State University Abstrak Dalam mempelajari bahasa Inggris, menulis merupakan salah satu ketrampilan yang sulit bagi siswa. Hal ini disebabkan karena siswa dituntut untuk mengungkapkan ide-ide mereka secara tertulis dengan susunan yang baik dan kosakata yang tepat. Melalui penggunaan media pembelajaran yang sesuai, siswa dapat terbantu untuk mengembangkan dan menyusun ide-ide mereka dengan baik. Video DreamWorks Animation merupakan salah satu jenis media yang dapat membantu dan mendorong siswa untuk menulis, khususnya menulis teks naratif, melalui gambar menarik di dalam video. Penelitian ini merupakan jenis penelitian eksperimental dengan desain dua kelompok dengan kelas XI-A1 (kelompok eksperimental) dan kelas XI-A2 (kelompok kontrol) di SMA Negeri 1 Cerme sebagai sampelnya. Peneliti memperoleh data melalui pre-tes dan pos-tes. Nilai-nilai pre-tes dan pos-tes dianalisis menggunakan Independent-samples T-test di SPSS. Hasil penelitian menunjukkan bahwa kelompok eksperimental memperoleh nilai pos-tes lebih tinggi (85.89) daripada kelompok kontrol (76.17). Selain itu, kelompok eksperimental juga memperoleh peningkatan dalam semua aspek ketrampilan menulis setelah memperoleh Kata Kunci: Ketrampilan menulis, video DreamWorks Animation, ketrampilan menulis teks naratif. Abstract Writing is one of the difficult skills for the students in learning English. It is because they have to express their thoughts in a written form with a good organization and the correct vocabulary. Through applying an appropriate media, they are helped to develop and organize their thoughts better. DreamWorks Animation video is a kind of media which can help and support them in writing, especially narrative text through the interesting moving pictures on the video. This research is an experimental research with two groups design with XI-A1 (experimental group) and XI-A2 (control group) of SMA Negeri 1 Cerme as the sample. The researcher collected the data through conducting pre-test and post-test. The scores were analyzed by using Independent-samples T-test on SPSS. The result showed that the experimental group scored higher (85.89) than the control one (76.17) in post-test. Also, the experimental group got an improvement after given the treatment in all writing aspects. Keywords: writing, DreamWorks Animation video, Writing narrative ability. INTRODUCTION English has become an international language which is used by people in the world. This reality can be seen from many sectors, such as economy, industry, tourism, education, etc. People use it to communicate with others in order to reach their goal based on their own sector and also create a good interaction. Another reality which shows English as an international language is many textbooks are written in English, for example travelling books, English magazines, science books, and so on. People who do not have a capability in using English cannot get information that they need. Also, many factories determine having good English capability with a certain standard as one of their requirements that have to be qualified. Therefore, mastering English is an important thing to be done by them. In education sector, English is a foreign language that has to be learnt. In Indonesia, it is taught at all schools from elementary level up to educational level. There are four skills in English that have to be learnt by the students, namely listening, speaking, reading, and writing. It is based on standard competence which stated that the purpose of learning English is to help the students understand English and they can develop their skills. That is why, the English educational system in Indonesia gets attention from the government, remembering its role as a foreign language. One of four skills that has to be mastered by the students is writing. Writing is the mental work of inventing ideas, thinking about how to express them, and organizing them into statements and paragraphs that will be clear to a reader (Nunan, 2003:88). This means that someone who wants to write has to accumulate all his / her ideas in a written form properly. Cimcoz (1999) added that students do not know how to write, feel stupid when they cannot find the right words, fear criticism and want to avoid the emotional turmoil experienced when they faced with a topic and blank piece of paper. It can be said that some students have already found something in their mind to be written, but they do not have ideas in how to write it. That is why writing becomes one of skills in English which is difficult to be learnt. To master writing, there are some aspects which have to be focused by the writer, for example the diction, the organization, and the grammar uses. Therefore, this skill cannot come immediately to the students. They have to do practicing. It is in line with Zhang and Cheng (1989:34) who explained that in writing activities especially writing in a foreign language, the writer should be able to use grammar, vocabulary, conception, rhetoric, and other elements. So that, in order to master writing, they have to be hard-working in doing it. Based on standard competence, there are many types of texts which have to be learnt by the students. They are transactional – interpersonal, short functional text, and genres. Focusing on genres, there are two kinds of genres : story and factual genres. Narrative, recount, and anecdote belong to story genres, while procedure, report, descriptive, and news item belong to factual. In this research, the researcher focuses the students’ level at the eleventh graders. So that, for the eleventh graders they have to learn report, narrative, analytical exposition, spoof, and hortatory exposition. They also have to express the meaning of those text types in a written form. Narrative text is chosen by the researcher in conducting this research. Here, in choosing the text type, the researcher has to look up at the syllabus of the eleventh graders first to know the correct lesson which they have not learnt yet in the second semester. In this semester for the eleventh graders, they learn narrative, spoof, and hortatory exposition texts. Because this research was conducted at the beginning of the second semester and the first text for the eleventh graders is narrative, so the researcher can do the research in appropriate time. Narrative is a kind of text which has a function to retell a particular story. To write a narrative text, the students have to comprehend some elements, such as the time words, grammar, and characteristics of the text. Therefore, it is common for them if they think that writing makes them confuse. They have to know each characteristic and generic structure of all texts which is different. Nevertheless, they do not need to feel afraid to do writing. Fegerson and Nickerson (1992:7) said “ Writing is a skill that is acquired through study. So, if you have ever felt afraid to write because of you were worried about making error, remember that making mistakes in writing is a stage that everyone passes through. “ To help students writing narrative text, the teacher has to help his / her students in writing. Briggs (1970) defined that media is physical means which are used to send messages to the students and stimulate them to learn. Media is anything used to send message(s) from the sender(s) to the receiver(s) , so it can be aroused the learners’ thought, feeling, and interest to gear the students’ learn (Sadiman et al, 2002). Referring to those definitions, the researcher can conclude that media is important to be applied in order to motivate the students to write. There are many kinds of media that can be used for the teacher in helping the students, such as visual, audio, audio-visual, tactile, and virtual. Therefore, in order to help the students, the use of media is important. Here, the researcher chooses one kind of audio-visual media to help the students in learning writing – that is, a video. Mayer (2001) states that video is a form of multimedia that conveys information through two simultaneous sensory channels: aural and visual. It often uses multiple presentation modes, such as verbal and pictorial representations in the case of on-screen print and closed-captioning. It means that the students can enjoy the pictures on the video and the information given at the same time. So that, they will be inspired to develop the content of the video which they have watched. However, there are many kinds of video which can be used for teaching – learning process, such as educational, cartoon, etc. Here, the researcher chooses videos from DreamWorks Animation SKG, Inc. in helping the students to write narrative text. DreamWorks Animation SKG, Inc. (DWA) is an American animation studio based in Glendale, California that creates animated feature films, television programs, and online virtual worlds. This studio produces many kinds of animated feature films, for example films, short films, and television series. To achieve the research objective of this research, the researcher chooses short films. The duration of short films which are produced by DreamWorks Animation SKG, Inc. is around 20 minutes or less. Therefore, they can be shown in one meeting and also they can be repeated at the same time if the students have not get the ideas of the videos yet. That is why, DreamWorks Animation videos are chosen by the researcher to improve the students’ ability in writing narrative text. Based on the background of the study, the researcher formulates the research question as follow: Is there any improvement of the students’ writing narrative ability after the researcher uses DreamWorks Animation videos in teaching writing narrative text ? RESEARCH METHOD Referring to the research question which had been mentioned before, the researcher chose experimental research with two groups design (experimental and control) as the research design. The experimental group is a group which is given the treatment, while the control group is a group which is not given the treatment. By using this design, the researcher wanted to know whether the use of DreamWorks Animation videos will improve the students’ writing narrative skill. Depending on the type of this research which is experimental, so there were two kinds of variables. They are independent and dependent variable. In this research, the independent variable was the use of DreamWorks Animation videos, while the dependent variable was the students’ writing narrative ability since the use of DreamWorks Animation videos can improve the students’ writing narrative ability. In this research, the population was the eleventh grade students of SMAN 1 Cerme Gresik. This school has ten classes of eleventh graders which are divided into six classes of science program (XI-A1, XI-A2, XI-A3, XI-A4, XI-A5, and XI-A6), three classes of social program (XI-S1, XI-S2, and XI-S3), and one class of language program (XI-B). However, in choosing the sample, the researcher chose purposive sampling method, because the researcher selected the sample from population with a particular reason. The first reason was to choose two classes which have similar ability in English. The second one was keeping the validity of the data. After the researcher chose the sample, the researcher randomly decided the experimental and control group. The result is XI-A1 as the experimental group and XI-A2 as the control one. Due to the type of this research which is experimental, the instrument needed by the researcher was data in the form of scores. Therefore, the researcher used a test to get the data needed. There were two tests which were used by the researcher in conducting the data needed, they were pre-test and post-test. The tests were in the form of writing a narrative text. Pre-test was held before the treatment was applied in the experimental group, while post-test was held after the experimental group got the treatment. Before pre-test and post-test were held in experimental and control group, the researcher tested the reliability of the instrument which is going to be used in another class. The result of the reliability calculation was .90 which was above .80. This means that the result indicated very high r or very reliable. Therefore, the tryout test was reliable and can be used in pre-test and post-test. There were four steps in collecting the data. The first was conducting pre-test in both groups. It was done at 19th of February 2014. Next, applying the treatment to the experimental group. The first treatment was applied at 20th of February 2014 and the second treatment at 27th of February 2014. After that, the researcher conducted post-test in both groups at 28th of February 2014 (control group) and 6th of March 2014 (experimental group). The last step was scoring the students’ writing. In analysing the data, the researcher used Independent-samples T-test. It was used to know the equality of both groups before the treatment was applied. Besides, it was also used to know the improvement of the students’ ability in writing narrative text after got the treatment. If the experimental group scored higher than the control one in post-test, the treatment was recommended to be applied. RESULTS AND DISCUSSION In pre-test, it was found that the mean score of the experimental group was higher (77.43) than the control group (72.28). Although the experimental group scored higher, both groups had equal ability in writing narrative text. It can be seen from the Sig. value provided by Levene that was .061, which is above .05. Therefore, the treatment could be applied. After applying the treatment, the post-test was conducted to know whether the treatment improves the students’ writing ability or not. The result showed that the mean scores of the experimental group in post-test was 85.89, while the control group scored 76.17. This means that the experimental group scored higher than the control one. The experimental group got an improvement after got the treatment. The experimental group got an improvement in each writing aspects. In terms of content, the mean score of experimental group was 25.89, while the control group scored 22.90. In terms of organization, the experimental group scored 17.46, while the control group scored 16.00. In terms of vocabulary, the experimental group scored 17.68, while the control group scored 15.17. For the language use aspect, the experimental group also scored higher (20.82) than the control group (18.10). In terms of mechanics, the experimental group scored 4.00, while the control group scored 3.83. To support the result, the researcher had analyzed the students’ compositions from pre-test to post-test of both experimental and control groups. In pre-test, the student’s E8 (experimental group) composition got total score 79 (content = 24; organization = 17; vocabulary = 17; language use = 17; mechanics = 4), while the student’s C5 (control group) composition got total score 78 (content = 26; organization = 18; vocabulary = 15; language use = 15; mechanics = 4). Meanwhile, in post-test, the student’s E8 composition got an improvement. The total score was 89 (content = 26; organization = 19; vocabulary = 19; language use = 21; mechanics = 4). For the student’s C5 composition, the total score was 78 (content = 22; organization = 18; vocabulary = 17; language use = 18; mechanics = 4). After comparing the students’ compositions in the pre-test and the post-test between the experimental and control group, it can be seen that the experimental group got an improvement in all writing aspects, while for the control group, the improvement is only at the vocabulary and language use aspects. Thus, it can be concluded that using DreamWorks Animation videos improves the students’ writing narrative ability at all aspects. CONCLUSIONS Based on the results and the discussion, the researcher can conclude that the students’ writing narrative ability between the experimental and control groups is significantly different. In post-test, the experimental group that got the treatment scored higher (85.89) than the control group (76.17). This indicates that the use of DreamWorks Animation videos improves the students’ writing narrative ability. Therefore, the treatment is recommended to be applied by the teachers in teaching and learning process, especially teaching writing narrative text. REFERENCES Briggs, L.J. (ed.) (1977). Instructional Design: Principles and Applications. New Jersey: Englewood Cliffs. Cimcoz, Yesim.1999. Teaching ESL/EFL Students to Write Better, The Internet TESL Journal, Vol. V No. 10, October http://iteslj.org/ Fegerson, Laraine and Nickerson, Marie-Loiuse. 1992. All in One. New Jersey: Marie-Louise Prentice Hall. Mayer, R.E. (2001). Multimedia learning. Cambridge: Cambridge University Press. Nunan, David. 2003. Practical English Language Teaching. Singapore: Mc Graw Hill Companies, Inc.